Relationship between Peer Victimization and Anxiety of Pupils: Mediating Effect of Psychological Needs - Mao-Ling, Zhu (ETHICS IN PROGRESS, 2019)
The present study aimed to explore the effects of psychological needs on the relationship of peer victimization and anxiety. Methods: A sample of 889 4th, 5th and 6th primary school students in Guangxi Zhuang Autonomous Region were recruited with the measurement of Peer victimization Questionnaire, Psychological needs Scale and Anxiety Scale (SAS). Results showed that: (1) There were no significant gender and grade differences with respect to Peer victimization; (2) Significant negative correlations were found between all types of peer victimization and the subscales of psychological needs. In addition, significant positive correlations were found between all types of peer victimizationand, anxiety and significant negative correlations between all the subscales of psychological needs and anxiety; (3) Psychological needs partially mediated the relationship between Peer victimizationexperience and anxiety.